General Relativity Without Calculus A Concise Introduction to the Geometry of Relativity - Natario, Jose.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
(3z(BGeneral Relativity Without Calculus(3y (Boffers a compact but mathematically correct introduction to the general theory of relativity, assuming only a basic knowledge of high school mathematics and physics. Targeted at first year undergraduates (and advanced high school students) who wish to learn Einstein$1 (Bs theory beyond popular science accounts, it covers the basics of special relativity, Minkowski space-time, non-Euclidean geometry, Newtonian gravity, the Schwarzschild solution, black holes and cosmology. The quick-paced style is balanced by over 75 exercises (including full solutions), allowing readers to test and consolidate their understanding.s
1 Lorentz transformations -- 2 Minkowski geometry -- 3 Non-Euclidean geometry -- 4 Gravity -- 5 General relativity -- 6 The Schwarzschild solution -- 7 Cosmology -- 8 Mathematics and physics.
Keywords: Physics; Mathematics; Physics; Classical and Quantum Gravitation, Relativity Theory; Applications of Mathematics; Cosmology; Astrophysics and Astroparticles